The Eastern Orthodox Church : a new history - McGuckin, John Anthony (Yale University Press, 2020)
An insider's account of the Eastern Orthodox Church, from its beginning in the era of Jesus and the Apostles to the modern age In this short, accessible account of the Eastern Orthodox Church, John McGuckin begins by tackling the question "What is the Church?" His answer is a clear, historically and theologically rooted portrait of what the Church is for Orthodox Christianity and how it differs from Western Christians' expectations. McGuckin explores the lived faith of generations, including sketches of some of the most important theological themes and individual personalities of the ancient and modern Church. He interweaves a personal approach throughout, offering to readers the experience of what it is like to enter an Orthodox church and witness its liturgy. In this astute and insightful book, he grapples with the reasons why many Western historians and societies have overlooked Orthodox Christianity and provides an important introduction to the Orthodox Church and the Eastern Christian World.